2018
DOI: 10.1108/jcom-07-2016-0055
|View full text |Cite
|
Sign up to set email alerts
|

Crafting employee trust: from authenticity, transparency to engagement

Abstract: Purpose The purpose of this paper is to propose and test a model examining how three influential organizational factors – authentic leadership, transparent organizational communication, and employee engagement – are linked to employee trust. Design/methodology/approach This study conducted an online survey on a random sample of 391 employees across different industry sectors in the USA. Findings Authentic leadership, transparent organizational communication, and employee engagement directly and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 89 publications
10
65
1
Order By: Relevance
“…This study has shown that there is strong direct relationship between transparent communication and trust. it is consistent to prior research, according to (Jiang & Luo, 2018;Rawlins, 2008) which state that scholars of Public relations have consistently found that transparent communication provide various positive employee outcomes, such as employee trust contribution. Furthermore, the study shows that Accountability is a significant relationship with trust.…”
Section: International Journal Of Human Resource Studiessupporting
confidence: 91%
See 3 more Smart Citations
“…This study has shown that there is strong direct relationship between transparent communication and trust. it is consistent to prior research, according to (Jiang & Luo, 2018;Rawlins, 2008) which state that scholars of Public relations have consistently found that transparent communication provide various positive employee outcomes, such as employee trust contribution. Furthermore, the study shows that Accountability is a significant relationship with trust.…”
Section: International Journal Of Human Resource Studiessupporting
confidence: 91%
“…Which can comprise of several factors including lack of feedback, one way of flow of information but at the same time effective and transparent communication can result in positive outcome including employees trust, motivation and self-confidence. Public relations scholars have consistently found that various positive employee outcomes are achieved by transparent communication and which contributes to several positive employee outcomes including employee trust (Jiang & Luo, 2018;Rawlins, 2008). Due to emerging consideration of implementing change in organization, the significance of transparent communication is emerged.…”
Section: Background To the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Huang's definition captured two of the key concepts in OPR: trust and satisfaction. Trust continues to be a key variable of interest in relationship management studies (Rawlings, 2008;Paine, 2013;Jo & Shim, 2005;Jiang, 2016) particularly in relation to relationship outcomes.…”
Section: Introductionmentioning
confidence: 99%